PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANG PADA PT. KMI WIRE & CABLE TBK PERIODE 2012-2023 - Anggi Prasetyo; Edian Fahmy (Journal of Research and Publication Innovation, 2025)
This research aims to determine the relationship between liquidity (current ratio), profitability (return on assets) and debt policy (debt to equity ratio) of PT KMI Wire & Cable, Tbk for the 2012-2023 period. This research uses quantitative methods using SPSS version 26. And the analysis used in this research is descriptive analysis, classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination test with variable X1 Liquidity (current ratio), variable X2 Profitability (return on assets) and variable Y Debt Policy (debt to equity ratio). The research results of the variable Y is 0.005 < 0.05 and the calculated T value is (-3.637) greater than the T table of 1.833. Variable And the coefficient of determination (Adjusted R2) was 64.6%, while 35.4% was influenced by other variables that were not examined in this study.